PERAN KARAKTERISTIK INDIVIDU DAN KOMUNIKASI EFEKTIF TERHADAP KINERJA KARYAWAN - Siti Rohyana; Ristanti Akseptori; Arie Indartono (Program Studi D4-Manajemen Bisnis, Jurusan Teknik Bangunan Kapal, Politeknik Perkapalan Negeri Surabaya, 2023)
One aspect related to human resources that must be considered by the organization is employee performance. Performance is the level of achievement of results on the implementation of certain tasks. Based on the context of human resource development, the performance of an employee in a company is needed. Thisstudy aimed to determine the effect of individual characteristics and effective communication on employee performance in the sea transportation and shipping service company group. This study used a causal associative approach. The statistical test technique used was multiple linear regression analysis using SPSS 25, by distributed questionnaires to 41 respondents. The results of this study indicated that individual characteristics significantly influenced employee performance, while effective communication did not significantly influence employee performance. Based on the simultaneous test results obtained F-count 20.426 greater than F-table 3.238 which showed that simultaneously individual characteristics and effective communication affect employee performance. In addition to attention to technical competence, companies must also pay attention to these two variables in optimizing their performance. Employees who have good individual characteristics and high effective communication skills tend to have better performance. This research can be a reference for companies in managing human resources more effectively.